Analisis Semiotik Film Upstream 2024 Dalam Mengonstruksi Realitas Profesi Kurir Di Era GIG Economy - Audric , Pramesvari Teena; Fadeli, Muhammad; Setyarahajoe, Ratna (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2026)
The development of the gig economy has changed work patterns, including the courier profession which relies on digital platforms. This study analyzes how the film Upstream (2024) constructs the reality of the courier profession in the gig economy era using Berger and Luckmann's theory of social construction of reality. A qualitative descriptive approach is applied using Roland Barthes's semiotic analysis method, covering denotative, connotative, and mythical meanings, as well as the processes of externalization, objectivation, and internalization. Data were obtained from scenes, dialogues, and visual elements representing courier activities. The results show that the film Upstream constructs the courier profession as a job with pseudo-flexibility, income uncertainty, time pressure, and unbalanced work relationships, while emphasizing values of resilience and solidarity. At the denotative level, the film presents realistic work routines, the connotation reveals power imbalances and the myth constructs an ideology of sacrifice and technological authority. Through the stages of construction, the film forms a courier identity as a resilient worker vulnerable to systemic risks. In conclusion, Upstream reflects the social reality of gig workers while shaping audience understanding of digital work dynamics through semiotic signs.